Out-of-Hospital Emergencies in Children Under Palliative Home Care - Hauch, Holger; El Mohaui, Naual; Wolff, Johannes E. A.; Vaillant, Vera; Brill, Sabine; Schneck, Emmanuel; Ströter, Natascha; Sibelius, Ulf; Kriwy, Peter; Berthold, Daniel (Frontiers in Pediatrics, 2021)
Introduction: Specialized palliative home care (SPHC) enables children and adolescents with life-limiting illnesses and complex needs to receive care at home. In addition to controlling symptoms and stabilizing the psychosocial situation, crisis anticipation is a component of SPHC. Since the establishment of the reporting SPHC team, parents have called for additional help from emergency medical services (EMS) in emergency situations with unexpected frequency. Children with life limiting diseases could undergo invasive procedures and unhelpful treatments with uncertain consequences. The questions arose as to which factors led to the involvement of the EMS in a palliative situation, what therapy was performed and what outcome could be reached. Methods: Records of the pediatric SPHC patients and EMS call-outs in these children of the reporting SPHC-team in the central region of Hesse, Germany (population: 1.1 million) were retrospectively analyzed from 01.11.2014 to 01.05.2021. The causes of the call-outs, the existence of an emergency agreement, the National Advisory Committee for Aeronautics (NACA) score, EMS therapy and outcome were examined. Patient data included age, palliative-justifying diagnosis, duration and intensity of care, place of death and median overall survival (MOS) and palliative SHPC treatment. Results: In total, 172 patients were analyzed during the study period. There were 27 EMS calls for a total of 20 patients/families (= EMS group). Palliative illness or a complication was the most frequent cause of call-outs. The patients in the EMS group were significantly less likely to have a DNR order, required more home visits and telephone calls and were under SPHC care for longer. There was a significantly higher proportion of crisis interventions at home visits. The children in the EMS group died less often from the underlying disease. Of the remaining 152 patients (= non-EMS group), a significantly higher proportion had a European home country. Conclusions: Despite the introduction of the SPHC, parents still call the EMS. Good cooperation and joint training should be sought to prepare all those involved for future call-outs.